2013
DOI: 10.1364/oe.21.032450
|View full text |Cite
|
Sign up to set email alerts
|

Supercontinuum laser based optical characterization of Intralipid® phantoms in the 500-2250 nm range

Abstract: A supercontinuum laser based double integrating sphere setup in combination with an unscattered transmittance measurement setup was developed and carefully validated for optical characterization of turbid samples in the 500-2250 nm wavelength range. A set of 57 liquid optical phantoms, covering a wide range of absorption and scattering properties, were prepared and measured at two sample thicknesses. The estimated bulk optical properties matched well for both thicknesses, and with theory and literature, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 30 publications
5
98
0
1
Order By: Relevance
“…A series of slits between sample and detector further reduced the number of scattered photons captured in the unscattered transmittance signal. For a more extensive description of the measurement setup, the calibration and measurement procedure and a thorough validation, the reader is referred to Aernouts et al (2013). Moreover, this validation study showed the high repeatability and signal-noise ratio of the system to obtain the BOP of very turbid samples in the Vis/NIR (Aernouts et al, 2013).…”
Section: Measurement Of Bulk Optical Properties For Raw Milk Samplesmentioning
confidence: 88%
See 2 more Smart Citations
“…A series of slits between sample and detector further reduced the number of scattered photons captured in the unscattered transmittance signal. For a more extensive description of the measurement setup, the calibration and measurement procedure and a thorough validation, the reader is referred to Aernouts et al (2013). Moreover, this validation study showed the high repeatability and signal-noise ratio of the system to obtain the BOP of very turbid samples in the Vis/NIR (Aernouts et al, 2013).…”
Section: Measurement Of Bulk Optical Properties For Raw Milk Samplesmentioning
confidence: 88%
“…Both spheres were equipped with a Vis (400-1100 nm) and NIR (1100-2400 nm) detector. Unscattered transmittance (M U ) was measured in a separate path with the Vis and NIR detectors positioned 1.5 m behind the sample to limit the fraction of scattered photons collected by the detectors (Aernouts et al, 2013. To obtain sufficient unscattered transmittance signal, the sample was loaded in a thinner cuvette with a path length of 170 μm (Schott, Germany).…”
Section: Measurement Of Bulk Optical Properties For Raw Milk Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of liquid phantoms with known optical properties is based on intralipid-20% as a diffusive medium and on India ink as an absorber by using a water dilution of these two components. These components have been thoroughly characterized in terms of a reduced scattering coefficient and absorption coefficient for intralipid, and an absorption coefficient for ink, both with CW measurements 22,26,[42][43][44][45][46] and TR measurements. 26,47 The amounts of components to be mixed are solely determined by accurate weighing, which ensures that the concentrations are known with high accuracy.…”
Section: Phantom Constructionmentioning
confidence: 99%
“…This outgoing monochrome beam is then split by a polka dot beam splitter (Type 4-9101, Optometrics, Massachusetts, USA) which sends 10 % of the power to a reference detector (PDA100A, Thorlabs Inc., New Jersey, USA) to monitor the stability of the illumination system. This part of the setup and all used components are described in detail by Aernouts et al (2013). The remaining 90 % of the monochrome light from the monochromator is focused into an optical fiber (multimode, NA 0.22, 200-μm core diameter) and guided towards the second part of the setup.…”
Section: Spatially Resolved Laser Reflectance Setupmentioning
confidence: 99%